Assessing Oral Health Knowledge and Practices: A Study of Mothers and Children in Northwestern Nigeria - Khadijat Isezuo, Khadijat; Muhammad Sani, Usman; Muhammad Waziri, Usman; Garba Ilah, Bilkisu; Ibikunle, Adedayo; Olanrewaju Taiwo, Abdulrazaq; Adamu, Asma’u; Bello Jiya, Fatima (Al-Athfal: Jurnal Pendidikan Anak, 2023)
Purpose – To explore the knowledge, attitude, and practices regarding oral and dental health for mothers of children aged 6 months to 8 years and older children aged above 8 years to 15 years seeking healthcare in a tertiary health facility in the Sokoto metropolis.Design/methods/approach – A cross-sectional study was conducted between February and April 2022. Subjects included mothers of 6 months to < 8 years and children aged 8 to 15 years presenting with minor illnesses to the General outpatient clinic. A structured questionnaire and focus group discussion guide were used to collect the information. Data was analyzed using IBM SPSS version 25.Findings – Out of 238 participants, 128 children were 6 months to <8 years, while 110 were above 8 to 15 years old. Less than half of mothers, 46.9%, had inadequate knowledge, while 20.3% had adequate practices. Among the older children in this study, the proportion of those with good knowledge, attitude, and practice level of oral health was 60%, 61.8%, and 32.7%. There was a significant moderate positive correlation between knowledge and attitude scores but not practice for the 2 groups. Mothers’ education and fathers’ occupation were significantly related to good scores (p=<0.05). Mothers of children with primary teeth and older children with permanent teeth in this study all had poor oral and dental health practices. More awareness programs should be conducted in the community to target those with poor practices. Increasing female education and empowerment is also essential in this regard.Research implications/limitations – This research implies that from an early age, it is necessary to check oral and dental health to prevent infectious diseases.Originality/value – Oral and dental health is an essential aspect of primary health care and is a situation in which the mouth, teeth, and gums are healthy and free from any diseases. Parents, especially mothers, are responsible for maintaining good oral hygiene practices and inculcating good oral hygiene habits in children.Paper Type Research paper